The effect of plasma generated ozone for cold storage the broiler chicken meat - MERISA YULIANI, MERISA; MAHFUDZ, L D; NURWANTORO, NURWANTORO; NUR, M (Nusantara Bioscience, 2019)
Yuliani M, Mahfudz LD, Nurwantoro, Nur M. 2019. The effect of plasma generated ozone for cold storage the broiler chicken meat. Nusantara Bioscience 11: 12-17.  The aim of this study was to determine the effect of combination treatment washing chicken meat with three ozone concentrations in the water during 10 min and stored at 2-7?C without ozonation and with ozonation, on the shelf life of chicken meat. The study was conducted with a complete random factorial design (CRD) factorial pattern 3 x 2 with 3 replications. The data were analyzed by using analysis of variance (ANOVA). If the results were significant, the analysis followed Duncan's New Multiple Range Test (DMRT). The results of statistical analysis showed that average pH values, color scores intensity b * for brightness (yellowness) and Peroxide value (PV) showed significant differences (P